Reliability of central coding of patient reasons for encounter in general practice, using the International Classification of Primary Care - Helena Britt (Journal of innovation in health informatics, 1998)
Objective to assess the accuracy, intra- and inter-coder reliability of secondary, centralised coding of patient reasons for encounter (RFEs) with the International Classification of Primary Care (ICPC). Design Almost 150,000 RFEs were secondarily coded with ICPC in a centralised central coding situation by trained coders. Efforts were made to gain high coder reliability. A random sample of 2,369 RFEs was independently assessed for coding accuracy. A further sample of 162 RFEs were tested for inter-coder reliability by comparison with a gold standard and for intra-coder reliability by matched comparison of double coded RFEs. Setting primary health care. Subjects doctor_patient contact records. Main outcome measures Accuracy was qualitatively assessed as: absent; incorrect; acceptable but could be improved; correct. Inter- and intra-coder reliability: mean percentage correct scores calculated at ICPC chapter level, at individual rubric level and within each ICPC chapter. Results Only 1.8% of RFEs were missing, incorrect or needed improvement. Inter-coder reliability at ICPC chapter level was 91.7% and at rubric level, 81.8%. Intra-coder reliability was 96.2% at chapter level and 90.0% at rubric level. Reliability varied with ICPC chapter. Conclusion High coder reliability can be gained with ICPC in a central, secondary coding environment but training, an improved index and coding rules are required.